2014
DOI: 10.1210/en.2013-1842
|View full text |Cite
|
Sign up to set email alerts
|

Low-Oxygen Tension and IGF-I Promote Proliferation and Multipotency of Placental Mesenchymal Stem Cells (PMSCs) from Different Gestations via Distinct Signaling Pathways

Abstract: The microenvironment of placental mesenchymal stem cells (PMSCs) is dynamic throughout gestation and determines changes in cell fate. In vivo, PMSCs initially develop in low-oxygen tension and low IGF-I concentrations, and both increase gradually with gestation. The impact of varying concentrations of IGF-I and changing oxygen tension on PMSC signaling and multipotency was investigated in PMSCs from early (preterm) and late (term) gestation human placentae. Preterm PMSCs had greater proliferative response to I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 63 publications
(51 reference statements)
0
16
0
Order By: Relevance
“…A value of P < 0.05 was considered to be statistically significant. Supeno et al (2013) had testified that IGF-1 acts as controlling switch for long-term proliferation of neural stem cells, and IGF-1 can promote proliferation of placental mesenchymal stem cells (PMSCs) via distinct signaling pathways (Youssef et al 2014). So we used CCK-8 assay to investigate whether IGF-1 would affect proliferation of DPSCs in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…A value of P < 0.05 was considered to be statistically significant. Supeno et al (2013) had testified that IGF-1 acts as controlling switch for long-term proliferation of neural stem cells, and IGF-1 can promote proliferation of placental mesenchymal stem cells (PMSCs) via distinct signaling pathways (Youssef et al 2014). So we used CCK-8 assay to investigate whether IGF-1 would affect proliferation of DPSCs in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, for hybrid receptors which bind both insulin and IGF-I, the transmembrane subunits play a decisive role in recruiting intracellular mediators through their Tyr residues. This is common in muscle progenitors but also in fully differentiated cells [53][54][55][56][57] (Fig. 1B).…”
Section: Implications Of Igfs In Cardiac Epigeneticsmentioning
confidence: 98%
“…In this study, autocrine IGF-1 levels maintain an elevated baseline activity of ERK1/2 signaling required for enhanced self-renewal (higher OCT4), endodermal (higher CYP51) and mesodermal (higher SM22 α ) potential, but weakened neuronal potential (lower Nestin) [84]. Another growth factor which is basic fibroblast growth factor (bFGF) was shown to be required in maintaining stemness and proliferation in hESCs [31, 85] and in MSCs [80, 86, 87]. Further investigation showed that this bFGF effect was mediated via the IGF system that is upregulated by an autonomous expression of IGF-1R, IGF-1, and IGF-2, as shown in umbilical cord MSCs [86].…”
Section: The Role Of Igfs In Msc Multipotency and Self-renewalmentioning
confidence: 99%
“…A study, in human dental pulp MSCs (hDSCs), confirmed that IGF-1R is required for MSC multipotency and can be regarded as a selection marker for stemness, just similar to OCT4 and SOX2 [89]. In placental MSCs (PMSCs), IGF-2 is upregulated by low oxygen tension and is required to maintain MSC multipotency [80, 87]. Also, in neural stem cells (NSCs), IGF-2 was shown to play an important role in maintaining self-renewal [90].…”
Section: The Role Of Igfs In Msc Multipotency and Self-renewalmentioning
confidence: 99%